MAiD, Mental Disorders, and Vulnerability: How Common Responses to Vulnerability Concerns are Inadequate - Butcher, Loughran (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The concept of vulnerability is bandied about frequently in ongoing debates about medical assistance in dying (MAiD) and who should be eligible, but is often used as a broad catch-all phrase to capture some sort of risk or concern that people have. This imprecise usage obfuscates the concerns that opponents to MAiD have about expansion to include those suffering from mental disorders as the sole underlying condition. Since what is intended to be captured by the term ‘vulnerable’ is at times unclear, attempts to respond to or mitigate this vulnerability can miss the mark. Arguments from vulnerability against expanding access to MAiD point out social and/or systemic factors that may influence the choices of people living with mental disorders to access MAiD, such as lack of access to adequate care, stigma and discrimination, suicidality, and the correlation between mental disorders and low socio-economic status. However, the common response to concerns about vulnerability, made by those who argue for expansion, focus on highlighting current safeguards that are in place to ensure only those who are eligible for MAiD gain access. Under this view, vulnerability is determined by assessing individuals for eligibility. Those who cannot meet the eligibility criteria would not be permitted access. Yet, this entirely misses the concerns being raised that point to systemic or social sources of risk. Ensuring that the individuals who access MAiD meet the criteria is to ignore the reasons for accessing it in the first place.